German Grammar Glossary — Internet Based Digital Course Material (Training and Practice : Journal of Educational Sciences, 2012)
The blended learning German grammatical digital course material introduced in the presentation is for those who learnt German before but would like to refresh, practice and improve their existing knowledge. The students can familiarise themselves with the weekly study material and do the weekly assignments any time during the given week. Consequently, there is no need to discuss the entire material only the problematic areas during contact sessions. The industry-specific terminology and phrases used in the sample sentences and exercises help students to broaden their vocabulary. The course material can be accessed via the internet-based distance framework called 'moodle '. My presentation focuses on the structure and delivery of the course material and what experiences I had so far.